Chest Wall Mass in Infancy: The Presentation of Bone-Tumor-Like BCG Osteitis - Phumin Chaweephisal; Teesit Torchareon; Shanop Shuangshoti; Piti Techavichit (Hindawi Limited, 2020)
Chest wall mass in infancy is rare. Malignant lesions are more common than infection or benign tumors. This is a case of a 12-month-old girl who presented with a 2 cm mass at the right costal margin and poor weight gain. Chest radiograph demonstrated a moth-eaten osteolytic lesion at the 8th rib. The resection was performed, and a mass with pus content was found. The positive acid fast stain (AFB) organism was noted. Pathology confirmed caseous granulomatous inflammation compatible with mycobacterial infection. However, QuantiFERON-TB Gold was negative, so Mycobacterium bovis (M. bovis) osteitis is highly suspected. She was treated with antimycobacterium drugs and showed good results. Osteomyelitis can manifest by mimicking bone tumors. Without a biopsy, the pathogen may go undetected. So, interventions such as biopsy are warranted and avoid mass resection without indication. High C-reactive protein (CRP), alkaline phosphatase (ALP), periosteal reaction of radiating spicules, and penumbra sign in magnetic resonance imaging (MRI) are helpful for discriminating osteomyelitis from bone tumor.